Artikulasi Hadith Muhammad Asad - Amir, Ahmad Nabil (Al Mabhats : Jurnal Penelitian Sosial Agama, 2022)
Abstract: This paper discusses Muhammad Asad's seminal work, Sahih al-Bukhari: The Early Years of Islam, first published in 1935 by The Arafat Publications, Srinagar, Kashmir, and had a second impression in 1981 by Dar Al-Andalus, Gibraltar. The work provides a modern translation and commentary of Sahih al-Bukhari, which is significant in terms of the philosophy and principles of hadith commentary in a contemporary context. The paper aims to analyze the essential ideas developed by Muhammad Asad in his discussion of hadith and compare them with other critical works by classical and contemporary Muslim traditionists. The research was structured using descriptive, analytical, historical, and comparative methods. The study concluded that the work was influential and profound, reflecting a contextualist approach in expounding the meaning of hadith and its intrinsic philosophy and far-reaching social and spiritual implications. Asad's work sets forth required and highly effective commentary methods of Al-Bukhari's Sahih, Sahih al-Bukhari in the Early Years of Islam, which has immensely contributed to the revival of hadith tradition and analysis (sharh) in modern times. Abstrak: Penelitian ini bertujuan untuk menganalisis dan menelaah karya Muhammad Asad (1990-1992) berjudul Sahih al-Bukhari diterbitkan pertama kali pada 1935 oleh Arafat Publications. Kitab ini merupakan terjemahan dan komentar ke atas Sahih al-Bukhari, yang memuatkan syarah dan kritik hadith yang tuntas dan mengesankan terhadap riwayat-riwayat sahih, meninjau latar belakang para perawi, lafaz dan konteks periwayatannya. Kajian ini cuba melihat pengaruhnya dalam pemahaman teks-teks hadith klasik, serta falsafah dan nilai-nilai rasional dan spiritual yang cuba dikembangkannya dalam konteks sejarah yang moden. Ia mengenengahkan ide dan fikrah yang dirumuskan Asad tentang pemandangan hadith klasik dan membandingkannya dengan tinjauan ahli hadith semasa yang lain. Reka bentuk kajian adalah bersifat deskriptif, analitis, historis dan komparatif. Dapatan kajian menyimpulkan bahawa Asad telah memberikan sumbangan yang signifikan dalam penelitian hadith dalam merumuskan metode dan pemahaman dasar tentang prinsip dan falsafah hadith yang rasional dan kontekstual. Ia memberikan asas yang kuat dalam pengembangan prinsip dan kerangka syarah yang kritis, yang memuatkan komentar dan analisis sejarah yang mendalam terhadap Kitab Sahih. Karyanya berupaya merumuskan pertentangan-pertentangan hukum dan istinbat para fuqaha dan muhaddith dalam tradisi syarah dan turut merespon pertikaian-pertikaian asas yang dibangkitkan terhadap riwayat-riwayat hadith yang dipertikaikan.